The enabling environments for the digitalization of African agriculture - Baumüller, Heike; Addom, Benjamin K. (International Food Policy Research Institute, 2020)
This chapter explains the four pillars of digitalization for agriculture (D4Ag) and takes a closer look at two of those pillars that are required to build a strong enabling environment. D4Ag holds great promise for the transformation of African agriculture, but only if it is carried out holistically—that is, if it is well defined and appropriately deployed as part of broader agricultural and rural development strategies. In other words, digitalization must be understood as an agricultural development tool rather than a technological tool so that its application is problem- rather than technology-driven.